Clinical-pathological aspects of metastatizing ameloblastoma: a review of clinical cases (Research, Society and Development, 2022)
Metastatic ameloblastoma is a benign odontogenic tumor that is histopathologically compatible with conventional ameloblastoma, but with an evolutionary course associated with the development of distant metastases, mainly to the lung. Objective: To carry out an integrative literature review for a better understanding of this theme, emphasizing the clinical-pathological and radiographic aspects of metastatic ameloblastoma. Methodology: An integrative literature review was carried out through the PubMed - MEDLINE database, with the descriptors: Ameloblastoma, Metastasizing ameloblastoma, metastatic neoplasm and pathology, with eligibility criteria and collection of scientific articles in a period of three months. Results: Therefore, from this selection of articles, 8 full papers were found; of these, only 2 articles were duplicated in the search strategies, thus totaling 5 works selected after applying the eligibility criteria. Conclusion: It was observed that most cases occurred in the mandible, without gender predilection, with an average age of approximately 36 years. The most common metastatic site is the lungs. The follicular pattern is the most common in the metastatic lesion. Regarding treatment, there is no standard therapy.